Molecular characteristics and pathogenicity analysis of infectious laryngotracheitis virus isolated in China from 2015 to 2019 - Xuehui Zhang; Lihua Tang; Linqing Duan; Ruihua Yang; Kangchengyin Liu; Jing Zhao; Ye Zhao; Guozhong Zhang (Poultry Science, 2025)
The aim of this study was to investigate the molecular characteristics and pathogenicity of recently isolated ILTV strains from China, thereby augmenting our understanding of its prevalence. The complete genome sequences of seven ILTV strains obtained from China between 2015 and 2019 were determined by high-throughput sequencing. Phylogenetic analysis showed that six isolates (SD2015, GD2017, SYB2018, HB201812, HB201806, and TJ2019) were classified together with CEO vaccine strains, while only one isolates LN2018 belonged to the wild-type cluster. Recombination analysis revealed compelling evidence of probable recombination events existing in SD2015, HB201806, and LN2018. Compared to TJ2019 and LN2018, chickens infected with HB201806 exhibited more severe conjunctivitis symptoms and tracheal damage, as well as higher viral load and viral shedding in the trachea. These findings will provide valuable references for further understanding the epidemiological status of ILTV and developing effective control measures.